The role of monocytes in thrombotic disorders - Shantsila, Eduard; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2009)
Although, the main physiological role of monocytes is attributed to innate immunity (that is, phagocytosis) and the development of tissue macrophages and dendritic cells, the pathophysiological role of these goes far behind these (simplistic) limits. Indeed, monocytes constitute a major source of blood tissue factor, a key element of the extrinsic coagulation cascade. Monocytes actively bind to platelets, thus forming very prothrombotic monocyte-platelet aggregates. Additionally, these cells link inflammation and the procoagulant state observed in various prothrombotic conditions. However, monocytes are also crucial for successful thrombus recanalisation. In this article, we review the available data on potential mechanisms that link monocytes with thrombosis-related processes.
Keywords: Monocytes; thrombosis; tissue factor; monocyte-platelet aggregates